Η ποντιακή ταυτότητα της τρίτης γενιάς - Βεργέτη, Μαρία (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1992)
In the 1920s more than 230,000 Pontic Greeks took refuge in Greece from Asia Minor and the Soviet Union. The overwhelming majority of them were from Asia Minor. Migratory waves from the Soviet Union to Greece continued despite long interruptions, reaching peaks in 1939 and again from 1988 until now. The collective identity of Pontic Greeks in Greece is not a national or ethnic identity, because the group is part of a larger nation, the Greek nation, and it is not regional, because the geographical area of reference has been lost. The group migrated en masse from their place of origin and are not able to return. The methodology used in researching the causes and conditions of the formation and subsequent evolution of Pontic identity in Greece from the 1920s included 92 face-to-face interviews conducted in 1989 with members of different generations of Pontic Greeks. The biographical approach was used in these interviews, which provided most of the material from which the conclusions were drawn. Other approaches were also employed, such as participant observation during the period 1986-1992, in depth interviews with government officials on the conditions of urban and rural resettlement of first generation Pontic refugees, and information supplied by Pontic organizations in Athens. The collective identity of Pontic Greeks in Greece expresses a socio-psychological feeling of identification which springs not only from the common past, but also from the particular manner of integration and the kind of cultural, economic and ideological relationship of the group with the larger Greek group. Identity is not only cultural identity. The group by means of its activity and its relationship with the social environment defines identity and its social boundaries. Pontic identity today is seen by the third generation as the right to cultural and historical uniqueness. This differentation does not imply separatism, but on the contrary it is a cohesive factor in the evolution of the common Greek national identity. The overall national identity encompasses Pontic identity. This leads to the formation of a nationalist, rather than a regionalist ideology.